Histopathological changes in malignant melanomas of the choroid after cobalt plaque therapy. Issue 3 (March 1977) - MacFaul, P. A.; Morgan, G.
Abstract : A series of 23 eyes removed after cobalt plaque therapy for malignant melanoma of the choroid is presented, and the histological changes are described with particular reference to the presence or absence of necrosis in the tumours. In 17 of the 23 eyes no evidence of tumour necrosis was found, though all showed evidence of radiation changes in the adjacent tissues. Necrosis was found in 6 cases but was prominent in only 2, one of which was the only example of a mixed-cell tumour, the other 22 being spindle-cell tumours. Enucleation became necessary on average at about 32 months after treatment (23 out of 100 treated eyes) because of obvious failure of treatment with evidence of continued growth, or because of radiational complications leading to a painful blind eye. The 5-year survival rate was 86% compared with about 50% when the treatment is enculeation.